Interpretation of Rice Husk Ash on Geotechnical Properties of Cohesive Soil (Global Journals of Research in Engineering, 2012)
This paper demonstrates the effects of rice husk ash (RHA) on the geotechnical properties of soil in stabilized forms specifically strength, workability, compaction and compressibility characteristics. Therefore, laboratory tests such as compaction, Atterberg limits, free swell index, unconfined compressive strength, direct shear and consolidation tests for different percentages of RHA content and original soil samples were performed. These test results show that the soil can be made lighter which leads to decrease in dry density and increase in moisture content and reduced free swelling and compressibility due to the addition of RHA with the soil. Besides that the unconfined compressive strength and shear strength of soil can be optimized with the addition of 10% RHA content.
Keywords: RHA; Index Properties; strength properties; swelling and consolidations